1985
DOI: 10.1159/000132109
|View full text |Cite
|
Sign up to set email alerts
|

A viable calf with trisomy 22

Abstract: Karyotyping of eight malformed calves resulted in the detection of trisomy 22 in one calf. This calf had a hernia umbilicalis, a urachus fistula, and slight brachygnathia inferior. This trisomy was not associated with lethality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
1

Year Published

1987
1987
1991
1991

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…Viable trisomies have been reported in cattle, primarily for certain of the smaller chromosomes (33,34). Because the genetic content of U10 seems as great or greater than MMU 16, there may not be a possibility of viable trisomies for the U10 chromosome in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Viable trisomies have been reported in cattle, primarily for certain of the smaller chromosomes (33,34). Because the genetic content of U10 seems as great or greater than MMU 16, there may not be a possibility of viable trisomies for the U10 chromosome in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…1972). One case of trisomy 21 (Long, 1984) and one case of trisomy 22 (Mayr et al, 1985) were also reported. Of these 23 cases in cattle, 22 had severe congenital abnormalities and died in the neonatal period.…”
mentioning
confidence: 96%
“…We now report that a cow trisomic for chromosome 22 is fertile. A viable female Fleckvieh (Simmental) calf with trisomy 22 was described in an earlier paper (Mayr et al, 1985). No evidence for mosaicism was detected in either lymphocyte or fibroblast metaphases (see Mayr et al, 1985).…”
mentioning
confidence: 97%
“…A viable female Fleckvieh (Simmental) calf with trisomy 22 was described in an earlier paper (Mayr et al, 1985). No evidence for mosaicism was detected in either lymphocyte or fibroblast metaphases (see Mayr et al, 1985). Unlike human chromosome 21. none of the three chromosomes 22 of our trisomic cow had a nucleolus organizer region.…”
mentioning
confidence: 97%